Best Answer

Unfortunately, limitations of the browser used by Answers.com means that we cannot see most symbols. It is therefore impossible to give a proper answer to your question. Please resubmit your question spelling out the symbols as "plus", "minus", "times".

Q: What is 3t 1 when t -4?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

5t + 1

t+8 = 2-3t add 3t to both sides: 4t+8 = 2 take 8 away from both sides: 4t = -6 divide both sides by 4: t = -6/4 = -3/2

15

6t2 - 7t - 5 = (3t - 5)*(2t + 1) So (6t2 - 7t - 5)/(3t - 5) = 2t + 1 provided that t is not 5/3

You're looking to combine these two equations into one that uses only the terms x and y, right? In that case, we can take either of those equations, solve it for t, and plug it's results in place of t in the other equation: x = -3t + 4 y = t + 1 y - 1 = t x = -3(y - 1) + 4 x = -3y + 3 + 4 x = 7 - 3y You can of course solve this for y as well: -3y = x - 7 y = (7 - x) / 3

Related questions

if you mean T-3t+2t+4 (T and t is different variables):T-3t+2t+4=T-t+4if you mean t-3t+2t+4:t-3t+2t+4=4

4 solve t

T + 5 + 3T = 1 Simplify the terms, T and 3T (think 1 apple plus 3 apples) 4T + 5 = 1 Subtract 5 from both sides. 4T = -4 then divide both sides by 4 to get T by itself. T = -4/4 T = -1 To check, substitute T = -1 wherever you see T in your original equation. T + 5 + 3T = 1 (-1) + 5 + 3(-1) = 1 4 - 3 = 1 1 = 1 (check)

4+3t = 22 3t = 22-4 t = (22-4)/3 t = 6

It is an equation. Taking it step by step: 17 = 3t - 4 17 + 4 = 3t 21 = 3t 7 = t So the value of t is 7.

t+5+3t = 1(subtract 5 from each side)t+3t = -4(combine like terms)4t = -4(divide both sides by 4)t = -4/4t = -1

4

4t-1 = t+2 3t -1 = 2 3t = 3 t = 1

Gather like terms: 3t - t = 13 - 4 ie 2t = 9 so t =4½ Check: 3t = 13½ + 4 = 17½, 4½ +13 = 17½ QED

5t + 1

t+8 = 2-3t add 3t to both sides: 4t+8 = 2 take 8 away from both sides: 4t = -6 divide both sides by 4: t = -6/4 = -3/2

3(t - 2)(t + 1)